2006
DOI: 10.1091/mbc.e05-05-0443
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Deacylation by Bst1p Is Required for the Quality Control of Glycosylphosphatidylinositol-anchored Proteins

Abstract: Misfolded proteins are recognized in the endoplasmic reticulum (ER), transported back to the cytosol, and degraded by the proteasome. A number of proteins are processed and modified by a glycosylphosphatidylinositol (GPI) anchor in the ER, but the quality control mechanisms of GPI-anchored proteins remain unclear. Here, we report on the quality control mechanism of misfolded GPI-anchored proteins. We have constructed a mutant form of the ␤-1,3-glucanosyltransferase Gas1p (Gas1*p) as a model misfolded GPI-ancho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 73 publications
(99 reference statements)
2
93
1
Order By: Relevance
“…These results show that Gas1*p is indeed targeted for degradation by the ERAD-L pathway. Our results are different from those published previously reporting that deleting Hrd1p had no effect on Gas1*p turnover (Fujita et al, 2006).…”
Section: Pmt2p (Pmt2-ca)contrasting
confidence: 99%
See 2 more Smart Citations
“…These results show that Gas1*p is indeed targeted for degradation by the ERAD-L pathway. Our results are different from those published previously reporting that deleting Hrd1p had no effect on Gas1*p turnover (Fujita et al, 2006).…”
Section: Pmt2p (Pmt2-ca)contrasting
confidence: 99%
“…As can be seen in Fig. 2B, lanes 1-4 and graph, when expressed in wild-type cells Gas1*p is degraded with a half-life of roughly 1.5 hours, consistent with previous data (Fujita et al, 2006). When we tested deletion mutants of all membrane-bound Hrd1p complex components (Hrd1p, Hrd3p, Der1p,and Usa1p), we found that they stabilized Gas1*p whereas Pmt1p-Pmt2p complex in ER quality control deletion of Doa10p (the central component of the ERAD-C pathway) did not (Fig.…”
Section: Pmt2p (Pmt2-ca)supporting
confidence: 92%
See 1 more Smart Citation
“…Roles for the noncatalytic subunits include recognition of the peptide and glycolipid substrates (Signorell and Menon 2009), and, in the case of Gab1 and Gpi8, possible interactions with the actin cytoskeleton (Grimme et al 2004;File S4) Remodeling of protein-bound GPIs: Following GPI transfer to protein, both the anchor's lipid and glycan remodeled (Figure 6;Fujita and Kinoshita 2010). The earliest event, which occurs in the ER, is removal of the inositol acyl moiety by lipase-related Bst1 (Tanaka et al 2004;Fujita et al 2006a). Next, the sn-2 acyl chain of the diacylglycerol is removed by the ER membrane protein Per1 to generate a lyso-GPI , whereupon a C 26:0 acyl chain is transferred to the sn-2 position by Gup1 in the ER membrane .…”
Section: Gpi Anchoringmentioning
confidence: 99%
“…PGAP1 is a multiple membrane-spanning protein localized in the ER that contains a lipase motif (GxSxG) in the luminal portion. Inositol deacylation by PGAP1 is required for the efficient transport of GPI-anchored proteins from the ER to the Golgi, as described in Section D. In yeast, the reaction is also needed for the efficient degradation of misfolded GPIanchored proteins (38). In addition, inositol deacylation is indispensable for the following fatty acid remodeling described in Section C-4 (39).…”
Section: C-2 Inositol Deacylationmentioning
confidence: 99%